Implementasi Penilaian Pembelajaran Pada Kurikulum 2013 Mata Pelajaran Sejarah - Efendi, Irfan; Prawitasari, Melisa; Susanto, Heri (Lambung Mangkurat University, 2021)
The 2013 curriculum as a complement to the previous curriculum has been running for almost seven years in education in Indonesia. The view of most teacher still does not heed the system according to the assessment in the 2013 Curriculum (K-13) guidebook. Teachers still think that the assessment is only on cognitive assessment, especially in history subjects. This study aims to describe the Implementation of learning Assessment in the 2013 Curriculum for History Subjects in Class XI IPS at SMA Negeri 2 Banjarmasin. This study also use qualitative methods in obtaining information starting from interviews, documentation, and observations collected as a source of research. There are two sources of research used in research, namely primary sources and secondary sources. The result pf this study before conducting classroom assessment, the teacher made a lesson plan (RPP). The implementation of the assessment carried out by the teacher is different from that in the lesson plans and in the implementation in the classroom. When implementing it in the classroom the teacher only uses two attitude assessment and skills assessment. The teacher’s obstacle in implementing this assessment it the number of students who are assessed in one class, as well as the view of teacher who still thinks that the assessment is only on results of students, not on the process of how students achieve it.